Peran Detasemen Khusus 88 Anti Teror Kepolisian Negara Republik Indonesia dalam menanggulangi Paham Radikalisme Di Kota Ambon - Siauta, Dody Alfayed; Titahelu, Juanrico Alfaromona Sumarezs; Leasa, Elias Zadrach (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Densus 88 AT Polri received information and succeeded in thwarting a plan for amaliah or an act of terror against one of the churches in Ambon City, Maluku Province. As long as they survive, both the terrorists and the families of the suspected terrorists are still the responsibility of Densus 88 Polri.Purposes of the Research: to examine efforts to overcome radicalism and the obstacles faced by the Special Detachment 88 Anti-Terror of the Indonesian National Police in Ambon City. The type of research used in this research is empirical juridical. The research location is the Maluku Regional Task Force Densus 88 in Ambon City.Methods of the Research: empirical juridical. The research location is the Maluku Regional Task Force Densus 88 in Ambon City.Results of the Research: efforts to tackle radicalism by the Special Detachment 88 Anti-Terror of the Indonesian National Police in Ambon City are through a preventive strategy, namely carrying out surveillance activities; including closed supervision of suspected terrorists with the aim of collecting as much information as possible from suspected terrorists, both the personal data of the suspected terrorists and the daily activities of the suspected terrorists. The second is carrying out social identification activities (Idensos) as a deradicalization effort, namely by visiting ex convicts by providing assistance to ex convicts with the aim that ex convicts can be helped and can continue a better life as Indonesian citizens who are far from radicalism. Third, counter-radicalization efforts, namely collaborating with the Office of the Ambon City Ministry of Religion to provide counseling to various schools so that they can avoid radicalism. The next strategy is to carry out repressive efforts, namely taking action against suspected terrorists who will carry out acts of terror commonly called amaliah acts, both those that are still in the planning stages and after the implementation of terrorist acts. In addition, the obstacles faced by the Special Detachment 88 Anti-Terrorism of the Indonesian National Police in Ambon City include a lack of personnel both conducting surveillance and social identification, the lack of informants from the public who have direct contact with suspected terrorists, terrorist families and ex-terrorist convicts who are not willing to return to the notion of nationalism and still hold fast to the thoughts and understanding of radicalism.